Clinical and policy contexts for cancer care: Evidence from Denmark, Ireland and Ontario (Canada). (13th November 2019) - Morris, M; Landon, S; McKee, M; Nolte, E
Abstract: Background: We know there are large differences in cancer survival between countries. We know much less about why they exist and persist. In the International Cancer Benchmarking Partnership, we are seeking to understand the influences on patient journey in different countries. In this study we explore how health system factors impact on cancer care in Denmark, Ireland, and Ontario (Canada) to identify common themes, national specificities, and messages for other health care providers. Methods: We systematically analysed (i) cancer policy and strategy documents from the three jurisdictions, published between 1995-2014 (n = 20) and (ii) interviews with key informants representing government, health services providers, professional bodies and patient organisations (n = 25). We thematically analysed both datasets using NVivo. Results: Five themes emerged from the document review and were confirmed by interview: governance, quality assurance, service delivery, infrastructure and workforce. All three jurisdictions introduced a designated organisation to lead, monitor and, in Ontario, fund cancer services. Reducing wait times was prioritized, with the expansion of diagnostic capacity from the 2000s, for example. Concentrating services into fewer specialist centres was widely viewed as crucial for improving survival for some cancers. Yet policy intent was not always successfully realised on the ground, with lack of sustained investment, organisational barriers or logistical challenges impeding implementation. Jurisdictions face particular challenges maintaining and upgrading infrastructure and equipment, and recruiting and retaining critical staff, specifically in radiology and primary care. Conclusions: Cancer care is complex and understanding the interrelationships between factors acting at different levels of the health system is important to improve outcomes. Continued investment in infrastructure and people will be essential. Key messages: Countries face common challenges in creating health systems that optimise cancer outcomes. Sustained investment in equipment and human resources will be critical to optimise cancer care and survival.